Recasting paradigms of institutional analysis and stakeholder analysis in housing research - Sana Malik; Fariha Tariq (Journal of Urban Management, 2021)
In response to the global challenge of low-income housing provision, research on understanding the housing provision mechanisms has gained a reputation among emerging scholars and practitioners in architecture, urban development, housing, and public policy. An effective provision system entails the institutions and stakeholders comprehending their interrelations within the housing market context, lacking conceptual clarity. Challenging roles of institutions and stakeholders within the domain of housing provision necessitates the groundwork to study the contextual positions and relations of stakeholders as an analogous component and the analysis of institutional frameworks. The paper provides the theoretical foundations within the metaphorical bases for integrating the respective analytical approaches, i.e., institutional analysis (IA) and stakeholder analysis (SA), drawing on critical theoretical constructs. By analytical comparison of empirical evidence of IA and SA in housing research against the prompting keywords, critical reflections offer the conceptual foundation of new research agenda through IA-SA integrated approach. The study thereby advances the theoretical understanding between the regulatory level (institutions) and engagement level (stakeholders). It proposes a multi-level analysis process that complements the IA-SA integration for examining the provision systems in the context of low-income housing.
Keywords: 710; Housing analysis; Research paradigms; Institutional analysis; Stakeholder analysis